Household food consumption and wastage during the covid-19 pandemic outbreak: A comparison between Peru and Brazil - Cequea, M. M. (2021)
The COVID-19 pandemic has represented a major global challenge. In Latin America, both Brazil and Peru reported the highest levels of impact in terms of proportional infection and death rates. Within this context, this study sought to compare food consumption and wastage patterns in Peruvian and Brazilian households. For these purposes, the authors conducted a quantitative research study based on a self-reported online survey submitted during the pandemic outbreak. Results revealed that the intention of reducing food wastage and implementing leftover management routines are related to the economic value of wasted food. In addition, in both countries, shopping lists are used as planning elements, and food purchases are influenced by on-sale products. Leftover management is also similar in both countries, and the expiration date on the label is the most commonly used criterion for consuming or discarding food items. Nevertheless, within the framework of the health and economic crisis generated, opportunities for change toward the adoption of smarter and more sustainable purchasing behaviors are emerging for both households and companies, in addition to giving equal importance to environmental, social, and economic benefits. This research study provided insights into food consumption and food wastage behaviors in times of crisis, such as a pandemic.